Factors influencing intention to donate via social network site(SNS): From Asian’s perspective - Suaini Sura; Jongchang Ahn; Ook, Lee (Elsevier, 2017)
This study examined whether external factors, which are charity project, charity organization, Internet technology features and social network site (SNS) features influence people’s general attitude towards online donation and their intention to donate via SNS. An online survey was conducted based on the framework of factors influencing the intention to donate via SNS that was adapted from the literature review. Data from 258 respondents were used for analysis. Structural equation modelling was used to test the research model and hypotheses. The results indicated that the Internet technology features factor significantly contributes in influencing people’s general attitude towards online donation, and general attitude positively influences people’s intention to donate via SNSs. The full mediation effect of the general attitude towards online donation on the relationship between Internet technology features and intention to donate via SNS was found. However, charity project, charity organization, and SNS features were not significant factors in influencing people’s intention to donate via SNSs. The sample was limited to some Asian countries (preliminary Malaysia and South Korea). Thus, the results cannot be generalized to other countries. The findings suggest that non-profit organizations should focus on how to deal with the Internet issues, especially pertaining to security and privacy. Therefore, a mechanism for gaining donors’ trust to use the Internet, particularly in doing online transaction must be considered.